The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physrevb.84.184303
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics in the thermoelectric Zintl compound Yb14MnSb11

Abstract: The density of phonon states in the thermoelectric material Yb 14 MnSb 11 has been studied first by inelastic neutron scattering and second in an element-specific way by nuclear inelastic x-ray scattering. The low sound velocity of 1880(50) m/s as obtained from the density of phonon states can be identified as an important reason for the low heat transport in this system. The high melting temperature of Yb 14 MnSb 11 contrasts with the low energy of all phonons (<25 meV) and relates to an unusual lack of softe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…In that case, we find Γ AS = 1.99 and the same value of the bulk modulus than when using the Vinet EOS. We note that these two values are significantly higher than for most of the thermoelectric materials and even than for Zn 4 Sb 3 for which Caillat et al found Γ = 1.57 [2] (in a recent work an even smaller value (Γ = 1.35) has been found [64]). In the case of filled skutterudites such as RFe 4 Sb 12 that have roughly the same lattice thermal conductivity than ZnSb above 300 K, we have found previously Γ = 1.5 for the lattice Grüneisen parameter close to room temperature [68].…”
Section: Asmentioning
confidence: 50%
“…In that case, we find Γ AS = 1.99 and the same value of the bulk modulus than when using the Vinet EOS. We note that these two values are significantly higher than for most of the thermoelectric materials and even than for Zn 4 Sb 3 for which Caillat et al found Γ = 1.57 [2] (in a recent work an even smaller value (Γ = 1.35) has been found [64]). In the case of filled skutterudites such as RFe 4 Sb 12 that have roughly the same lattice thermal conductivity than ZnSb above 300 K, we have found previously Γ = 1.5 for the lattice Grüneisen parameter close to room temperature [68].…”
Section: Asmentioning
confidence: 50%
“…1) is a typical example of PGEC concept. 111,115 The large unit cell, complex structure and large number of atoms in the unit cell lead to intrinsically low lattice thermal conductivity. It is the best p-type thermoelectric material in the high temperature region so far (800-1275 K) and has a zT value of ~1.2 at 1275 K, doubling the efficiency of previous Si-Ge alloys and is currently being developed by NASA for high temperature radioisotope thermoelectric generators.…”
Section: √123+ 4 21mentioning
confidence: 99%
“…The thermoelectric material Yb 14 MnSb 11 provides an illustrative example: the unit cell contains 208 atoms with a unit cell volume greater than 6000 Å 3 . This feature, combined with a low sound velocity, produces a thermal conductivity near the glass limit . Another material with a very complex crystal structure, Gd 117 Co 56 Sn 112 , has 285 atoms per unit cell volume of 6858 Å 3 and an extremely low κL < 0.3 W/m‐K at room temperature …”
Section: Intrinsically Glass‐like Crystals: Anharmonicity Complexitymentioning
confidence: 99%